Engineering Docetaxel Micelles for Enhanced Cancer Therapy Through Intermolecular Forces - Hao Wang; Feirong Gong; Jiajie Liu; Lanlan Xiang; Yanfen Hu; Wenchen Che; Ran Li; Sisi Yang; Qixin Zhuang; Xin Teng (Bioengineering, 2024)
Docetaxel has exhibited excellent therapeutic effects in cancer treatment; however, its hydrophobicity, short blood circulation time, and high blood toxicity restrict its clinical application. The use of mPEG-PLA micelles to deliver docetaxel into the body has been verified as an effective approach to enhance its therapeutic efficacy. However, mPEG-PLA micelles are easily disassembled in the bloodstream, which can easily lead to premature drug release. To broaden the application scenarios of mPEG PLA micelles, we utilized the π–π stacking effect as an intermolecular force to design a novel mPEG-PLA-Lys(Fmoc) micelle to enhance the blood stability and permeability of drug-loaded micelles. The result showed that drug-loaded micelles for injection did not alter the tissue selectivity of docetaxel. Intravenous injection of the micelles in nude mice showed better antitumor efficacy than docetaxel injection and tumor recurrence rate is 0%, which is significantly lower than that of docetaxel injection (100%). The micelles designed by this research institute are anticipated to improve the clinical therapeutic effect of docetaxel.